2016
DOI: 10.1177/0886260516647006
|View full text |Cite
|
Sign up to set email alerts
|

Within and Inter-Institutional Differences Between Death Certifiers on Autopsy Conclusions

Abstract: This study seeks to establish whether medico-legal practitioners differ in their autopsy conclusions within and across medico-legal institutions. Data include 459 violent deaths (homicides, suicides, and accidents) autopsy reports written by more than 20 death certifiers from four medico-legal institutions in two countries (France and the United States). Multinomial models show that compared with accidental deaths, weapon use and decedents' characteristics both influence a homicide verdict, but not a suicide o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Heterogeneity of forensic investigation systems, within and across states, may impede accurate classification of suicide and other manners of death in the US [ 31 , 49 ]. With no national oversight, administration of death investigation systems varies from state control under an appointed state medical examiner to county control under an elected coroner or a medical examiner [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity of forensic investigation systems, within and across states, may impede accurate classification of suicide and other manners of death in the US [ 31 , 49 ]. With no national oversight, administration of death investigation systems varies from state control under an appointed state medical examiner to county control under an elected coroner or a medical examiner [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, if there were more studies addressing racial disparities in the manner of death determination [91,93,94], both at the national and regional levels, these studies could then be analyzed together to produce a more robust and specific effect size estimate of the effect of race on decisions in forensic pathology. Furthermore, research has demonstrated that there are individual-level and institutional-level differences in forensic science decision making [100][101][102], while the growing body of research into implicit cognitive bias in forensic science is certainly promising, clearly much work needs to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed lack of agreement and highlighted the fact that classifying the manner of death may not be as clear‐cut as some TV shows would have us believe. Further work has solidified these findings: not only a follow‐up on the original survey by Hanzlick, Goodin, and Haden‐Pinneri [37], but also work addressing different angles of this question, including some by this author [17], and other using experimental designs [11].…”
Section: Individual Decision‐makingmentioning
confidence: 92%
“…First, a statistical analysis of autopsy reports randomly selected from all four of the author's research sites [17] showed that men were more likely than women to classify deaths as homicides (or be assigned to homicides, this remains to be clarified) and that French medicolegal professionals were more likely than American ones to classify deaths as homicides. The latter finding makes sense within the larger institutional context presented earlier.…”
Section: Individual Decision‐makingmentioning
confidence: 99%
See 1 more Smart Citation